173 Debridement, Antibiotics and Implant Retention (DAIR) in the Management of Prosthetic Joint Infections Following Primary Hip and Knee Arthroplaty: A DGH Experience. (19th August 2022) - Feathers, J; Awad, F; Punjabi, S; Prasad, K; Silva, C; Sarasin, S; Lewis, P
Abstract: Aim: Prosthetic joint infections (PJI) are a devastating complication of arthroplasty surgery. Current gold standard one or two-stage revision, poses sincere surgical challenges and carry significant patient morbidity. If diagnosed promptly, a debridement, antibiotics, and implant retention (DAIR) procedure can be performed. We report the results of our experience with the DAIR procedure in a District General Hospital setting. Method: Our study comprises of a single centre retrospective review of a prospectively updated database. All patients who underwent a DAIR procedure following hip or knee arthroplasty from August 2012 to July 2019 were included in the study with no exclusions. Results: Four total knee replacements, sixteen total hip replacements (THR), two revision THR and three hemiarthroplasties were included in the study. Average duration from onset of symptoms to DAIR was 22 days for immediate post-operative patients and 6 days in patients presenting later with an acute infection. All patients had exchange of modular components during the DAIR procedure. Out of 25 DAIR procedures, 23 identified a positive microbiology culture. Most common causative organisms identified were Staphylococcos aureus (23%) and S taphylococcus epidermidis (23%). Average follow up in clinic was 55 months. 76% of patients had a stable post-operative recovery with no recurrence of infection. One patient required a revision THR for aseptic loosening; one patient required a knee arthrodesis and four patients died. Conclusions: Infection was successfully eradicated in 19 patients. The success reported within the literature stem predominantly from tertiary units. Our study reflects this success in a DGH setting.